The development of the actions of the educational inspection - Pérez, José Francisco; Jiménez Jiménez, Amor (Avances en Supervisión Educativa, 2021)
The educational inspection develops actions to carry out functions of control and supervision, evaluation and advice, and guidance and information. The fundamental task of these actions is, firstly, to try to ensure compliance with the laws, secondly, to ensure the guarantee of the rights and the observance of the duties of those who participate in the teaching and learning processes and, lastly, the improvement of the educational system and the quality of teaching. Precisely, the development of these actions, through their functions, involves the exercise of educational inspection.The implementation of these actions can be integrated or independent and cover a census or sample universe, following, however, a series of basic rules: that they have a procedure for their development and that they are based on principles and attributions.
Keywords: inspection actions; nature of inspection; inspection procedures